Gyrokinetic simulations compared with magnetic fluctuations diagnosed with a Faraday-effect radial interferometer-polarimeter in the DIII-D pedestal. (1st December 2022) - Curie, M.T.; Hatch, D.R.; Halfmoon, M.; Chen, J.; Brower, D.L.; Hassan, E.; Kotschenreuther, M.; Mahajan, S.M.; Groebner, R.J.; DIII-D team,
Abstract: Experimental data on electromagnetic fluctuations in DIII-D, made available by the Faraday-effect radial interferometer-polarimeter (RIP) diagnostic Chen (2016 Rev. Sci. Instrum. 87 11E108), is examined in comparison with detailed gyrokinetic simulations using gyrokinetic electromagnetic numerical experiment (GENE). The diagnostic has the unique capability of making internal measurements of fluctuating magnetic fields ∫ n e δ B r d R ∫ n e d R . Local linear simulations identify microtearing modes (MTMs) over a substantial range of toroidal mode numbers (peaking at n = 15) with frequencies in good agreement with the experimental data. Local nonlinear simulations reinforce this result by producing a magnetic frequency spectrum in good agreement with that diagnosed by RIP. Simulated heat fluxes are in the range of experimental expectations. However, magnetic fluctuation amplitudes are substantially lower than the experimental expectations. Possible sources of this discrepancy are discussed, notably the fact that the diagnostics are localized at the mid-plane—the poloidal location where the simulations predict the fluctuation amplitudes to be smallest. Despite some discrepancies, several connections between simulations and experiments, combined with general criteria discriminating between potential pedestal instabilities, strongly point to MTMs as the source of the observed magnetic fluctuations.